Experimental Study of Two-Stage Anaerobic Co-Digestion of Corn Steep Liquor and Agricultural Wastes for Hydrogen and Methane Production Including Metagenomics - Elena Chorukova; Galina Stoyancheva; Lyudmila Kabaivanova (Applied Sciences, 2025)
This study investigated the dynamics and composition of microbial communities within the bioreactors of a two-stage anaerobic system employed for the bioconversion of corn steep liquor, a food processing byproduct, into hydrogen and methane. The high organic matter content of such wastes positions them as valuable substrates for biotechnological applications. The two-stage anaerobic digestion (AD) process was compartmentalized into a hydrogen-producing bioreactor (3 dm3) and a methane-producing bioreactor (15 dm3), each harboring distinct microbial consortia. The system yielded a maximal hydrogen production of 1.02 L/day and a peak methane production of 24.1 L/day with substrate corn steep liquor and cattle manure in a ratio 1:1. Microbial consortia were recognized as critical drivers of AD performance and biofuel yield. This research demonstrated the efficacy of a two-stage approach, segregating the hydrogenic (hydrolysis and acidogenesis) and methanogenic (acetogenesis and methanogenesis) phases, for optimized energy recovery from the co-digestion of corn steep liquor and cattle manure under controlled conditions. Metagenomic sequencing and a subsequent bioinformatics analysis were utilized to characterize the microbial diversity within each bioreactors. These findings contribute to a deeper understanding of the microbial ecology of AD and hold the potential for broader applications in waste-to-energy bioconversion.